2008
DOI: 10.1111/j.1863-2378.2008.01109.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Seroprevalence to Coxiella burnetii (Q fever) in Northern Ireland

Abstract: Despite the widespread prevalence of infection with Coxiella burnetii, there have been few large population-based studies examining the epidemiology of this infection. The aim of this study was to examine the distribution and determinants of C. burnetii past infection in Northern Ireland (NI). Coxiella burnetii phase II specific IgG antibodies were measured by enzyme-linked immunosorbent assay in stored serum from 2,394 randomly selected subjects, aged 12-64, who had participated in population-based surveys of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
56
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 17 publications
9
56
2
Order By: Relevance
“…In the only study conducted in recent years (2010), the prevalence of IgG phases I and II of C. burnetii was reported at 24% and 36%, respectively, in febrile patients of Kerman Province (southeast Iran) ). In the present study, age and length of employment were correlated parameters and had a positive significant association with the seroprevalence of Q fever, and these findings are consistent with other similar studies (McCaughey et al 2008, Anderson et al 2009). Studies conducted around the world have shown that livestock is the main reservoir for Q fever in humans (Angelakis and Raoult 2010).…”
Section: Discussionsupporting
confidence: 82%
“…In the only study conducted in recent years (2010), the prevalence of IgG phases I and II of C. burnetii was reported at 24% and 36%, respectively, in febrile patients of Kerman Province (southeast Iran) ). In the present study, age and length of employment were correlated parameters and had a positive significant association with the seroprevalence of Q fever, and these findings are consistent with other similar studies (McCaughey et al 2008, Anderson et al 2009). Studies conducted around the world have shown that livestock is the main reservoir for Q fever in humans (Angelakis and Raoult 2010).…”
Section: Discussionsupporting
confidence: 82%
“…Cases of hepatitis and pneumonia have however been reported in children and can be fatal [93, 200]. In Northern Ireland, McCaughey et al [201] reported a seropositivity rate inferior to 10% in children. The seropositivity rate increased markedly during the late teenage years and especially in young adults [201].…”
Section: Epidemiological and Clinical Aspectsmentioning
confidence: 99%
“…In Northern Ireland, McCaughey et al [201] reported a seropositivity rate inferior to 10% in children. The seropositivity rate increased markedly during the late teenage years and especially in young adults [201]. Increased exposure with age is a plausible hypothesis to explain this phenomenon.…”
Section: Epidemiological and Clinical Aspectsmentioning
confidence: 99%
“…Since 2007, Q fever has become an important public health problem in several parts of Europe (McCaughey et al 2008;Karagiannis et al 2009;Panaiotov et al 2009;Schimmer et al 2009). Although Q fever in humans is asymptomatic in more than 60 per cent of cases, it may lead to either an acute or a chronic disease (Raoult et al 2000).…”
Section: Introductionmentioning
confidence: 99%